A Review for Functionally Gradient Materials Processes and Useful Application (Journal of University of Babylon for Engineering Sciences, 2018)
Abstract In the science of materials, the term Functionally Graded Materials (FGMs) which could be recognized by the gradual changes in structure and composition leading to variation in the characterization of materials. (FGMs) is considered one of the recent development of composite materials to enhance the strengths and reduce the weaknesses of these materials. (FGMs) were used for the first tiMe in Japan in 1984 via an airplane project because these materials could be used and designed for many roles and applications. The reasons that make (FGMs) are multi-function materials due to the variation in the chemical composition, microstructure and design features depending on the requirements. In this review, the functionally graded materials are studied on many different sides such as the application (the field of implementation) of this new technology and the reason of each use. Moreover, discuss the manufacturing processes for functionally graded materials and discuss the reason of choosing each process. On the other hands, discuss the limitation of the using functionally graded materials were taking in the consideration.